Skateboarding in High School Physical Education Classes (Research, Society and Development, 2023)
This research is based on the importance of teaching skateboarding in Physical Education classes in high school, and many teachers find it difficult to teach and plan adventure body practices classes. The objective of this article is to present the elaboration and evaluation of the application of a pedagogical proposal for teaching skateboarding in Physical Education classes in high school. The methodology is characterized as qualitative, being guided by the ethnographic framework of everyday school practice. The research had two stages: 1) Elaborate a pedagogical sequence for teaching skateboarding in Physical Education classes in high school; 2) Evaluate the application of the pedagogical sequence through analysis of a focus group. As a data collection instrument, the focus group was used, applied to the students participating in the research after the pedagogical intervention of the elaborated proposal. The results indicated that thematic skateboarding in high school Physical Education classes can contribute with a set of knowledge that goes beyond concepts and practices, reflecting on attitudes that collaborate in the lives of students in society. Therefore, it is essential that school Physical Education classes go beyond models restricted to traditional sports, in which only modalities with balls and practices that students are exhausted from practicing throughout basic education are offered.